Capital Movements and Environmental Harms - Christopher Dick; Andrew K. Jorgenson (Journal of World-Systems Research, 2015)
The authors engage appropriate macrosociological theorization and employ quantitative comparative methods to assess the extent to which various forms of environmental degradation in less-developed countries are tied to inward foreign direct investment in the primary and secondary sectors. Analyzed outcomes include carbon dioxide emissions, industrial organic water pollution, and deforestation. Such forms of environmental harms are known to partially shape migration processes as well as other social dynamics. Results of longitudinal analyses indicate that all three forms of environmental degradation are positively associated with sector-level inward foreign direct investment, which provides broad support for the engaged theoretical orientation.